Analysis of Science Literacy of Physics Education Students at UIN Walisongo Semarang Using the PISA Model Test Instrument - Fariyani, Qisthi; Nisak, Nurul Kholifatun; Safitri, Ida (Physics Education Research Journal, 2025)
This study aims to analyze the level of science literacy at the Physics Education Study Program UIN Walisongo Semarang by using the International Student Assessment (PISA) Model Test Instrument. Science literacy is measured based on the ability of students in analyzing, applying concepts, and using a scientific approach in the context of basic mechanics, especially in business material, energy, and power. This study involved students of Physics Education UIN Walisongo Semarang with test data showing the highest score of 84, lowest 16, and an average of 32 of the maximum score of 100. Analysis of the indicator of competency achievement shows a significant variation between the eight aspects measured. The highest indicator is the ability to analyze and apply the concept of relationship between business and kinetic energy and potential energy (39%), followed by the application of scientific methods in the concept of kinetic and potential energy (36%). Meanwhile, the lowest indicator is found in the aspect of analyzing and applying the concept of relationship between business and mechanical energy changes (16%) as well as the application of scientific methods in the concept of mechanical energy (26%). These findings indicate that students tend to experience difficulties in integrating scientific approaches and complex conceptual understanding. The results of this study indicate that the literacy of physics education students is still at a low level, with the dominance of factual and conceptual abilities that have not fully developed to the analytical and applicative levels. Therefore, innovation is needed in the learning approach and assessment that is oriented towards strengthening scientific thinking and transfers cross -context concepts. This study made an important contribution in the development of PISA -based science literacy assessment for higher education in the field of physics education, as well as supporting the strengthening of 21st century competencies in science education in Islamic tertiary institutions.